Inter-Clonal Variations in Fruit Parameters in a Clonal Seed Orchard of Teak (Tectona grandis L.) - Behera, Manoj Kumar; Bhol, Nirakar (Indian Forester, 2016)
Information on inter-clonal variations in reproductive parts of any tree species can better guide and assist us in the selection of better genotypes. A study was conducted in a 33 year old Clonal Seed Orchard (CSO) of Teak (Tectona grandis) comprising of 13 different clones from two distinct provenances of Angul district of Odisha, India to record the inter-clonal variations in regard to the fruit characteristics. The fruit length and fruit width of the clones studied varied significantly and ranged from 1.49 to 1.68 cm and 1.31 to 1.54 cm, respectively. Clone ORANR3 was found to bear fruits having highest length and width while the fruits of clone ORANP7 occupied the lowest value in both the parameters. The weight of 100 fruits was found be maximum under ORANR6 (49.13gm). On the other hand, clones like ORANP3, ORANP6 and ORANP7 were found to register lowest fruit weight. Most of the fruits of ORANR1 were found viable (70.38%) whereas, fruits of ORANP4 showed the least viability (37.31%). The role of traits like weight of 100 fruits and fruit viability for further selection and tree improvement programme to obtain superior genotypes was established with the expression ofhigh heritability and moderate genetic advance values. A moderate correlation (0.19) was found between fruit weight and viability of seeds.